Fundamentals and Applications of Surface-Enhanced Raman Spectroscopy (SERS) - López-Ramírez, María Rosa; Otero-Fernández-de-Molina, Juan Carlos; Soto-Martín, Juan; Castro, Jose Luis; Arenas Rosado, Juan Francisco (My University, 2019)
When a molecule is adsorbed on some metallic nanostructured surfaces such as silver, copper or gold, it can undergo an enormous enhancement of the Raman signal giving rise to the so called Surface-Enhanced Raman Scattering (SERS). The high sensitivity of this effect allows an accurate structural study of adsorbates at very low concentrations. The SERS effect has historically been associated with the substrate roughness on two characteristic length scales. Surface roughness on the 10 to 100 nm length scale supports localized plasmon resonances which are considered as the dominant enhancement mechanism of SERS (Electromagnetic Enhancement Mechanism: SERS-EM). It is usually accepted that these electromagnetic resonances can increase the scattered intensity by an average factor of ca. 104 to 107. A secondary mechanism often thought to require atomic scale roughness is referred to as Charge Transfer (CT) Enhancement Mechanism (SERS-CT). This mechanism involves the photoinduced transfer of an electron from the metal to the adsorbate or vice versa and involves new electronic excited CT states which result from adsorbate–substrate chemical interactions. It is also estimated that such SERS-CT mechanism can enhance the scattering cross-section by a factor of ca. 10 to 102. These two mechanisms can operate simultaneously, depending on the particular systems and experimental conditions, making difficult to recognize each one and to estimate their relative magnitude in a particular spectrum.
Keywords: Nanopartículas; SERS; Nanoparticle